Dual Regulation of Notch1 Signaling Pathway by Adaptor Protein Fe65 - Kim, Mi-Yeon (American Society for Biochemistry and Molecular Biology, 2012)
Notch1 receptor functions as a critical controller of cell fate decisions and also as a key regulator of cell growth, differentiation, and proliferation in invertebrates and vertebrates. In this study, we have demonstrated that the adaptor protein Fe65 attenuates Notch1 signaling via the accelerated degradation of the membrane-tethered Notch1 in the cytoplasm. Fe65 also suppresses Notch1 transcriptional activity via the dissociation of the Notch1-IC-recombining binding protein suppressor of hairless (RBP)-Jk complex within the nucleus. Fe65 is capable of forming a trimeric complex with Itch and membrane-tethered Notch1, and Fe65 enhances the protein degradation of membrane-tethered Notch1 via an Itch-dependent proteasomal pathway. Collectively, our results demonstrate that Fe65 carries out different functions depending on its location in the regulation of Notch1 signaling.